Orthorexia nervosa tendency among students of the department of nutrition and dietetics at a university in Istanbul - KARAVUŞ, MELDA; HIDIROĞLU, SEYHAN (KARE PUBL, 2017)
OBJECTIVE: The aim of this study was to determine an orthorexia nervosa scale score for and evaluate orthorexic tendency among students of nutrition and dietetics according to various sociodemographic characteristics. METHODS: This cross-sectional study was carried out in May and June of 2016 among 208 students in the nutrition and dietetics department at a university in Istanbul. After receiving the approval of the university ethics committee, of a total of 300 students, 208 agreed to join the study. Participants completed a questionnaire related to individual characteristics and the ORTO-11 scale during a face-to-face interview. The ORTO-11 scale is a verified Turkish scoring system in which a low score indicates orthorexic tendency. The Mann-Whitney U test, independent samples t-test, Kruskal-Wallis test, and analysis of variance were used to assess the data. P<0.05 was accepted as statistically significant. RESULTS: Orthorexic tendency was significantly higher in males (p=0.050) and students who lived with their family (p=0.002). Mean ORTHO-11 scale score did not differ significantly between groups when the participants were grouped by parameters of smoking, alcohol consumption, chronic disease status, body mass index, diet observance, or use of nutritional supplement products. CONCLUSION: The orthorexic tendency was higher in men and in students who lived with their family. Additional assessment of individual eating habits, eating behavior, and personality characteristics would shed light on the reasons for the difference between gender groups. Qualitative studies should be carried out and possible confounding factors should be determined.
Keywords: Eating behavior disorder; food choice; orthorexia; EATING-DISORDERS; PREVALENCE; RISK